Preparação de LiNbO3 e LiNbO3:Eu3+ pelo método dos precursores poliméricos - Souza, Luciana A. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Fredericci, Catia; Lanciotti Jr., Francesco; Pizani, Paulo S. (Sociedade Brasileira de Química, 2002)
The ferroelectric compound LiNbO3 was prepared by the polymeric precursors method in the polycrystalline form containing different concentrations of Eu3+. The compounds were characterized by X-ray diffraction, vibrational and electronic spectroscopy. Electronic spectroscopy was shown to be sensitive to small concentrations of contaminating phases allowing a good control of the compound purity. The presence of Eu3+ ions leads to the formation of the LiNb3O8 phase in the range of 500 to 800 °C. Above this temperature range LiNbO3 and tetragonal (T') EuNbO4 were obtained.
Preparation of LiNbO3 and LiNbO3:Eu3+ by the polymeric precursors method
Keywords: Pechini method; lithium niobate; europium luminescence